Roswell : The Complete Second Season Disc 6 Episodes 20-21 - Patrick R Norris; Appleby, Shiri, 1978- (USA 20th Century Fox, 1999)
Living among the citizens of the infamous New Mexico city of Roswell are four who are not there by choice. They are there to follow a destiny given to them by the members of their dying race, a race that they are someday destined to save. This is the background behind the WB series "Roswell". Max Evans, Isabel Evans, Michael Guerin and Tess Harding are teenage humans with extraordinary gifts - gifts that are "not-of-this-earth". They are human/alien hybrids, sent here as replacements for the royalty of an alien race. Their counterparts have already perished in a war of attrition, thus one day, the "royal four" will return to their home planet and save their race. Before a fateful day in 1999, the teens hid their gifts. The event that forever changed their lives was when Max healed Liz Parker (a classmate) after she was fatally shot in the stomach in a dispute between two customers at the restaurant where she waitresses. A close relationship then developed between Max and Liz. It was later mirrored by a relationship between Liz's best friend Maria Deluca and Michael. Central to the first season were the relationships between the hybrids and their human companions. That focus has shifted during the drama's second season. "Roswell" is now distinctly a science-fiction show built on the relationships between humans and aliens.
Languages: English, French Subtitles: English, French
Keywords: Drama; Mystery; Romance; SciFi; Thriller -- Tv Series